Neurodevelopmental Status of Infants Conceived Assisted Reproductive Techniques in Royan Institute - Ramin Mozafari Kermani Kermani; Leila Nedaeifard; Mohamad Nateghi; Abolhasan Fazeli (Tehran University of Medical Sciences, 2011)
Objective: There is a large amount of information published about ART infants worldwide but apparently the similar data did not published by Iranian ART centers till now. This study is a comparative study for developmental assessment of these infants. Materials and methods: In one case- control study 400 ART ' infants have been compared with 420 NC ' infants. Their developments have been assessed two times with test of Denver II until 9 months old. All of them were citizen of Tehran and assessed in one center. They have been adjusted for duration of pregnancy and delivery result. Chi- Square test and Wilcoxon Singned Ranks test were used for analysis of data. Results: From 400 infants of ART, 31/3% was preterm and 42/8% were multi fetal pregnancy, which were higher than NC. There was not significant difference in development of infants of ART and NC in different methods of ART in two times assessment (without concerning premature and multi fetal pregnancy) (P>0/05). There was not significant difference between development of term and single fetal pregnancy of ART and NC in first and second time of assessment of development (p values were 0/7 and 0/4 respectively). Conclusion: We concluded that there is not any difference in development of term and single fetal pregnancy in infants of ART and NC until 9 months old.